Workload Analysis of Registration Personnel and Medical Records: Approach Method Workload Indicators of Staffing Need - Dwi Sulistyowati; Elsye Maria Rosa (Universitas Aisyah Pringsewu, 2023)
The quality of Human Resources is very influential on performance in an organization in general and work units in particular. Each work unit requires a workforce under its main tasks and functions with the number of workers according to the standard. This study aims to analyze the Workload Analysis of Registration and Medical Record Workers with the Workload Indicators of Staffing Need (WISN) approach. The research method uses a mix method approach. This research was carried out in the second trimester of 2022 at the registration and medical record unit at R. Ali Manshur Hospital Tuban. There were five research samples, namely the Director (interview), HR Manager (1 person), Casemix Team (1 person), Head of Registration and Medical Records Unit (2 people), and Implementers in the registration and medical record unit (5 people). In conducting qualitative data analysis to understand the data obtained, it is necessary to use a thematic analysis. The steps that will be carried out in the study include Observation (Observation), Interviews with personnel in each shift, and Viewing documents. The results of the study indicate that the need for personnel for registration is four and four for the medical record unit. Abstrak: Kualitas Sumber Daya Manusia sangat berpengaruh pada kinerja dalam suatu organisasi pada umumnya dan unit kerja pada khususnya. Setiap unit kerja membutuhkan tenaga kerja yang sesuai dengan tugas pokok dan fungsinya dengan jumlah tenaga sesuai standar. Tujuan penelitian ini menganalisis Analisis Beban Kerja Tenaga Pendaftaran dan Rekam Medik dengan pendekatan Workload indicators of Staffing Need (WISN). Metode penelitian menggunakan pendekatan mix method. Penelitian ini dilaksanakan pada tribulan dua tahun 2022 di Unit pendaftaran dan rekam medik RSUD R. Ali Manshur Tuban. Sampel penelitian berjumlah lima, yaitu Direktur (wawancara), Manager SDM (1 orang), Tim Casemix (1 orang), Kepala Unit Pendaftaran dan rekam medis (2 orang) dan Pelaksana di unit pendaftaran dan rekam medis (5 orang). Dalam melakukan analisis data kualitatif untuk memahami data yang didapatkan maka perlu menggunakan tematik analisis. Langkah-langkah yang akan dilakukan dalam penelitian meliputi Pengamatan (Observasi), Wawancara kepada personal di tiap shif dan Melihat dokumen. Hasil penelitian menunjukkan bahwa kebutuhan tenaga untuk pendafataran sebanyak empat 4 orang dan untuk unit rekam medis sebanyak enam.